Effect of Zhi Tune Music on Motor Function of Cerebral Ischemic Stroke Hemiplegic Patients with Qi Deficiency and Blood Stasis Syndrome - Xia LI; Feng DENG; Xiaoyu WU; Jinxiu CHEN (康复学报)
Objective:To explore the effect of Zhi tune music on motor function of cerebral ischemic stroke hemiplegic (CISH) patients with Qi deficiency and blood stasis syndrome.Methods:A total of 90 CISH patients with Qi deficiency and blood stasis syndrome were randomized into Zhi tune group (n=45) and conventional control group (n=45). Zhi tune group accepted listening to music of Zhi tune in addition to general treatment and care while conventional control group only received general treatment and care. The treatment lasted for four weeks in both groups. The Fugl-Meyer assessment scale, clinic neurological function deficit scale for stroke, and traditional Chinese medicine (TCM) symptomatic grading and quantifying standard were used to evaluate the therapeutic effect of both groups.Results:After the treatment, the upper and lower extremities'FMA scores of both groups were increased significantly (P<0.05), and the increasing amplitude of lower extremities'FMA score of Zhi tune group was higher than that of conventional control group (P<0.05). The neurological function deficit scales of both groups after the treatment were decreased significantly (P<0.05), and the decreasing amplitude of Zhi tune group was higher than that of conventional control group (P<0.05). The TCM symptomatic therapeutic effect of Zhi tune group was better than that of conventional control group (P<0.05).Conclusion:Zhi tune music could improve motor function of lower extremities, repair nervous functional deficiency, and improve TCM syndrome of CISH patients with Qi deficiency and blood stasis syndrome.